Unexpected Crossroads of International Political Communication: Influence and Insights of Universal Codes of Media as Exemplified by Podcasts, Comics and New Media - Yeromin, Mykola (Mediaforum : Analytics, Forecasts, Information Management, 2021)
The article dwells upon the original research conducted by author during and after his PhD studies. Through the case studies of media (exemplifying podcasts, comic books and unclassifiable new media such as web-series) directly influencing and/or vice versa being influenced directly by current political events, shown is the interconnecting tissue of universal codes of media, affecting the international political communication through media influence in unpredictable ways. Underlined is the crucial need to strengthen the awareness of experts and general population alike of such processes in Ukraine due to hybrid war occurring with Russian Federation.